Formulation and Evaluation of Nano Co-Crystal Based Oral Disintegrating Tablet of Ezetimibe - Puneeth, J; Sudheer, Preethi; John, Shiji; PR, Darshan; Y, Jyothi (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Low solubility, poor permeability, and hepatic drug degradation are the primary factors responsible for the poor bioavailability issues of orally administered drugs. Ezetimibe, a biopharmaceutics classification system (BCS) Class II anti-cholesteremic drug, has a bioavailability between 35% and 65% due to its substantial intestinal and first-pass metabolism. Objectives: An alternative method for drug administration is to be attempted on an orally disintegrating Ezetimibe tablet to avoid low bioavailability, as mentioned earlier. Materials and Methods: The solubility issues of the drug were tackled by converting the drug into nano co-crystals using nicotinamide as a coformer utilizing the solvent anti-solvent method, followed by spray drying. The formulations were optimized using a custom experimental design. The optimum nano co-crystal formulation was converted into an orally disintegrating tablet using crospovidone as a super disintegrating agent and evaluated. Results: Nano co-crystals solubility was 0.030 to 0.049mg/mL. The release of the drug in a pH of 6.8 phosphate buffer was found to be 027.100.011 to 30.02;0.003%. Compatibility studies by FTIR confirm the absence of the drug's reaction with the excipients. X-ray, as well as DSC, indicated reduced Ezetimibe's crystalline nature. The disintegration time of ODT was marked down as 28 sec. ODT's in vitro release profile in PBS p 6.8 reveal a 20-fold increase in drug release compared to the pure drug. Conclusion: Therefore, ODTs containing nano co-crystals of Ezetimibe could provide a better alternative to improve solubility and the dissolution rate, which may enhance the bioavailability.
Keywords: Ezetimibe; Micro crystalline cellulose; Oral Disintegrating Tablets; Nano co-crystals; Fast release; Dissolution